2014
DOI: 10.1117/1.jbo.19.8.085001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating femtosecond-laser-induced two-photon photoacoustic generation

Abstract: We investigated two-photon absorption-based photoacoustic generation and compared it with corresponding photoluminescence emission. Experimental results revealed expected quadratic dependences on the incident optical fluence in both photoacoustic and photoluminescence processes. We also investigated the influence of optical scattering on the generation of two-photon photoacoustic and photoluminescence signals and found that photoacoustic signals attenuated more slowly than photoluminescence signals when the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…This nonlinear relationship, analogous to other nonlinear microscopies, such as two-photon fluorescent microscopy 18 and two-photon absorption-induced PAM, 19,20 can significantly improve the axial resolution of GR-PAM. In this work, an intensity-modulated CW laser, instead of a nanosecond pulsed laser as in Ref.…”
Section: Methodsmentioning
confidence: 77%
“…This nonlinear relationship, analogous to other nonlinear microscopies, such as two-photon fluorescent microscopy 18 and two-photon absorption-induced PAM, 19,20 can significantly improve the axial resolution of GR-PAM. In this work, an intensity-modulated CW laser, instead of a nanosecond pulsed laser as in Ref.…”
Section: Methodsmentioning
confidence: 77%
“…With multimodal microscopy, we can obtain a more comprehensive insight into the tissue microarchitecture in living animals, including the vasculature, neurons, and extracellular matrix. A recent study has reported that an amplified femtosecond laser could excite two-photon photoacoustic signal 34 . So in future, we may try to use an amplified femtosecond laser to replace the two independent lasers in this system.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, OR-PAM has succeeded in suboptical-diffraction imaging, taking advantage of various nonlinear mechanisms such as two-photon absorption, 79-81 photobleaching, 82 absorption saturation, 83 and thermal relaxation. 83,84 Nonlinear OR-PAM has provided optically determined resolutions in all dimensions including the axial or depth direction.…”
Section: Optical-resolution Patmentioning
confidence: 99%